Análise do nexo causal entre atividade desenvolvida e doença ocupacional/afastamentos médicos de servidores técnicos-administrativos em educação da Universidade Federal de Mato Grosso - Dall'Apria, Giovana Rodrigues (2021)
The present research is a study developed with the general objective of carrying out an analysis of the causal nexus between developed activity and occupational disease / medical leave of active employees in the career of TechnicalAdministrative in Education (TAE) of the Federal University of Mato Grosso (UFMT), in the sixyear period 20142019. As specific objectives, it was proposed to: a) Characterize the sociodemographic profile, of illness and mental illness of active employees in the career of UFMT TAEs, through the analysis of the records of licenses for health treatment approved in the Integrated Health Care Subsystem. Server Health (SIASS); b) Identify the possible relationships between registered cases of illness and mental illness and the activities developed by active employees in the career of UFMT TAEs, through the articulation between statistical analysis and the general literature on the social identity of the career; and c) Establish the possible factors that motivate the leave of active civil servants in the career of TAEs, from UFMT, through the procedure of identifying the profile of the most exposed civil servants and / or those prone to leave for treatment due to health reasons. Methodologically, it consisted of retrospective observational research composed of two phases: the first carried out the characterization of the investigated sample from the search and analysis of institutional documents that allowed the description of the workers in scope; and the second investigated the profile of illness through systemic records of absence from work activities for health reasons, added to the institutional data that portrayed the course of these absences for the period in question. The analyzes were contextualized by reviewing the scientific literature in the area of Mental Health & Work, using Le Guillant's French Psychosociology as a theoretical lens. As a result, it was identified that some dimensions marked a more significant change in the sociodemographic profile of UFMT TAEs during the sexennium in scope, since it was noted the composition of a predominantly young workforce scenario, in terms of age and time of effective exercise in the institution, as well as it was observed that the public office of TAE was, also, the first public office occupied by many workers in the period. Regarding the studied illness records, especially mental illness, it was identified that the leave due to Mental and Behavioral Disorders (CMD) were the minority. Most departures from TAEs approved by the Medical Examination, of the University, in the sexennium in question, were concentrated under the diagnostic classification of the ICD10 Z. However, overall, there was a worsening of the situation regarding the number of subjects affected by TMC over time. The analysis of the average duration of each leave, by ICD F, proved to be superior to that of other homologous diagnostic classifications in the period. Depressive symptoms were present among the TAEs, from UFMT, throughout the study period. The analysis of the profile of the servers most exposed and / or prone to licenses for health treatment resulting from TMC indicated a predominance of servers with up to 10 years of service.